Luminous pervious concrete and preparation method thereof

By using spaced-grade coarse aggregate and modified luminescent powder, the problem of difficult to take into account the compressive strength and water permeability of existing luminescent concrete is solved, and efficient water permeability and stable luminescent performance are achieved.

CN119661148APending Publication Date: 2025-03-21JIANGSU TAILIN ENG COMPONENTS CO LTD

Patent Information

Application Number
CN202411739067.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

It is difficult for existing luminescent and water-permeable concrete to take into account both compressive strength and water-permeable properties, and the luminescent powder is easily affected by hydrolysis reactions during concrete mixing, resulting in a degradation of luminescent performance.

Method used

The modified luminescent powder is used to improve its thermal stability in high temperature and hydration environment by combining silica coating and sodium borate thermal stabilizer.

Benefits of technology

The compressive strength and water permeability of luminescent and water permeability are improved, while ensuring the long-term maintenance of the chemical stability and luminous properties of luminescent powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to luminous pervious concrete and a preparation method thereof. The luminous permeable concrete is prepared from the following raw materials in parts by mass: 280-300 parts of cement, 870-900 parts of interval grading coarse aggregate, 70-80 parts of modified luminous powder, 30-40 parts of fly ash, 4-6 parts of a water reducing agent, 20-30 parts of a water repellent agent, 30-40 parts of epoxy resin, 3-5 parts of a silane coupling agent and 90-100 parts of water, and the interval grading coarse aggregate is prepared by mixing coarse aggregate with a small particle size of 4.95-9mm and coarse aggregate with a large particle size of 12.5-10mm according to a mass ratio of 1: 2; the surface of the modified luminescent powder is coated with silicon dioxide sol, and sodium borate is added for heat-resistant treatment. The light-emitting water-permeable concrete has compressive strength and water permeability, the light-emitting property is stable, and the hydrophobic and oleophobic corrosion resistance in the concrete is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to luminous permeable concrete and a preparation method thereof. Background Art

[0002] Pervious concrete, also known as porous concrete or permeable concrete, is a concrete material with high porosity. Compared with traditional concrete, pervious concrete allows water to pass through its structure, thus having good water permeability. In urban road construction, water concrete is not only conducive to road drainage, but also can absorb the noise generated by the friction between wheels and the road surface, improve driving safety and comfort, and is a key component of sponge city construction. In addition, if concrete has a luminous function while having permeability, it will not only add color to the construction of the city, but also in some remote sections of the road at night, power outages or emergency escape moments, the ground signs can play a great role, so luminous pervious concrete has broad application prospects.

[0003] At present, there are few studies on permeable concrete with both light storage and luminescence properties. Patent document CN 117383874A discloses a colored luminous permeable concrete and its preparation method. The concrete uses oxysilane hydrophobic materials and permeable additives to enhance the internal hydrophobicity of the luminous permeable concrete, and the luminous function is achieved by laying luminous stones on the surface of the permeable concrete. However, it is worth thinking about that, on the one hand, the concrete pursues permeability and uses a single-graded coarse aggregate, which cannot take into account both compressive strength and permeability; on the other hand, the method of achieving the luminous function by laying luminous stones lacks integrity, and the luminous stones are exposed for a long time, which reduces their service life.

[0004] Therefore, it is considered to add luminescent materials to the concrete mixing process. During this process, the luminescent powder will absorb water and undergo hydrolysis reaction in a humid environment, thereby affecting its luminescent performance. Patent document CN118206905A discloses a road water-based energy storage luminescent coating and its preparation method and application, which uses silicon film grafting modification technology to achieve coating protection of strontium aluminate rare earth alkali metal aluminate powder to improve its water resistance. On the other hand, hydration heat is generated during the concrete molding process. As the temperature rises, the thermal motion inside the luminescent powder material intensifies, resulting in more excitation energy being released through non-radiative transitions (such as phonon scattering) rather than through radiative transitions (luminescence), thereby affecting its luminescent performance. Therefore, for the luminescent powder mixed in concrete, it is necessary to improve the thermal stability in high temperature or hydration heat environment in summer.

[0005] Therefore, in order to solve the above problems, a luminous permeable concrete that is more in line with the use requirements is needed. Summary of the invention

[0006] In view of this, the purpose of the present invention is to propose a luminous permeable concrete and a preparation method thereof, so as to solve the problem that single-graded coarse aggregate luminous permeable concrete cannot take into account both compressive strength and permeability and the concrete preparation process affects the luminous performance of the luminescent powder.

[0007] Based on the above purpose, the present invention provides a luminous permeable concrete, which is prepared from the following raw materials in parts by mass: 280-300 parts of cement, 870-900 parts of interval-graded coarse aggregate, 70-80 parts of modified luminous powder, 30-40 parts of fly ash, 4-6 parts of water reducer, 20-30 parts of hydrophobic agent, 30-40 parts of epoxy resin, 3-5 parts of silane coupling agent and 90-100 parts of water; the interval-graded coarse aggregate is prepared by mixing 4.95-9 mm small-size coarse aggregate and 12.5-10 mm large-size coarse aggregate, and the mass ratio of the small-size coarse aggregate to the large-size coarse aggregate is 1:2.

[0008] By adopting the above technical solution, coarse aggregate with interval grading is used. Compared with single-graded coarse aggregate, there are more contact points in the voids of the coarse aggregate with interval grading, which improves the compressive strength. In addition, the more stable and uniform pore structure is also conducive to enhancing the permeability.

[0009] Furthermore, the preparation process of the modified luminescent powder is as follows: S1: dissolving tetraethyl orthosilicate in anhydrous ethanol, adding nitric acid as a catalyst for hydrolysis reaction, and stirring and mixing thoroughly to form silica sol; S2: Strontium silicate luminescent powder and strontium aluminate luminescent powder are mixed in a ratio of 1:1 and added to the silica sol in batches, and ammonia water is added to adjust the pH to 9-10. The mixture is stirred at 75-90°C for 0.5-1h for polycondensation to form silica gel. The silica gel aggregates on the surface of the luminescent powder and forms a dense coating layer, which is filtered and dried to obtain the coated luminescent powder. S3: Slowly add 10-20% sodium borate solution of half the mass of the coated luminescent powder into the above-mentioned coated luminescent powder, stirring while adding, mix evenly at a temperature of 100-150°C, and dry to obtain a modified luminescent powder.

[0010] By adopting the above technical scheme, the luminescent powder with a silica coating has better hydrophobic and corrosion-resistant properties, avoiding the influence of the strong alkaline environment with a pH of up to 12 and the possible hydrolysis reaction during the concrete mixing process. Sodium borate is added as a thermal stabilizer. Sodium borate can decompose at 100-150°C to form borate glassy substances. As a protective layer, it can reduce the non-radiative transitions caused by thermal motion in the high-temperature environment of luminescent concrete hydration, ensuring the stability of its luminescent performance.

[0011] Furthermore, the cement is silicate cement.

[0012] By adopting the above technical solution, the surface of silicate cement easily absorbs water to form silanol groups with strong polarity, and the silanol groups easily entangle with other surface modifiers to form a network structure.

[0013] Furthermore, the small-size coarse aggregate is at least one of limestone and sandstone, and the large-size coarse aggregate is at least one of granite, dolomite and cedar.

[0014] By adopting the above technical scheme, the color of the above coarse aggregate rock is light or gray, which is beneficial to improving the luminous performance of the luminous transparent concrete; the use of limestone and sandstone can improve the thermal conductivity and wear resistance of permeable concrete. Limestone and sandstone also have good cementing properties and can be evenly dispersed in permeable concrete, making the concrete pore distribution more uniform and the pore structure more stable; the use of high-hardness rocks such as granite, dolomite and cedar stone improves the compressive strength of concrete. Further, the fly ash is Class II fly ash.

[0015] By adopting the above technical scheme, fly ash has good spherical particles and fine particle size, which can improve the fluidity of concrete, reduce the viscosity of the mixture, and make concrete easier to mix and pour.

[0016] Furthermore, the water reducer is an aminosulfonate-based high-efficiency water reducer.

[0017] By adopting the above technical scheme and adding aminosulfonate-based high-efficiency water-reducing agent, the consistency of permeable concrete is improved, so that the permeable concrete is not prone to bleeding or segregation during mixing and transportation, which is beneficial to the uniform distribution of coarse aggregate in the permeable concrete, making the density of the permeable concrete more uniform, and further beneficial to improving the compressive strength of the permeable concrete.

[0018] Furthermore, the hydrophobic agent is tridecafluorooctyltrimethoxysilane.

[0019] By adopting the above technical scheme, the tridecafluorooctyltrimethoxysilane molecule contains a long fluorocarbon chain and has a very low surface energy, so that the permeable concrete is not easily wetted by oil and organic matter, and exhibits oleophobic properties; tridecafluorooctyltrimethoxysilane is hydrolyzed to generate silanol and methanol, and the generated silanol further undergoes a condensation reaction to form a siloxane bond, forming a hydrophobic film on the surface of the concrete, so that the permeable concrete is not easily corroded by water, and the permeable concrete is not easy to age, which is beneficial to extending the service life of the permeable concrete; the surface of silicate cement easily absorbs water to form silanols with strong polarity, and the silanols easily react with silanols to form siloxane bonds, which is beneficial to the entanglement between molecules to form a network structure, which is beneficial to improving the consistency of the permeable concrete and enhancing the compressive strength of the permeable concrete.

[0020] Furthermore, the epoxy resin is a bisphenol A epoxy resin, and the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and methacryloxysilane.

[0021] By adopting the above technical scheme, epoxy resin is used as a binder for bonding the luminescent powder and various components of concrete, thereby improving the integrity of the luminescent permeable concrete. Epoxy resin has excellent chemical stability, can resist the erosion of acids, alkalis and solvents, and improves the corrosion resistance of permeable concrete. According to the principle of similar miscibility, both silane coupling agent and silicate cement contain silicon element, which is beneficial to improve the compatibility of various components in permeable concrete, making it easier to disperse the various components in permeable concrete evenly. At the same time, when the silane coupling agent plays a coupling role, it needs to be hydrolyzed to form silanol. The silanol contains silanol with strong polarity. The silanol on the silanol is easy to form hydrogen bonds with the silanol and amide groups on the surface of silicate cement, which is beneficial to the entanglement between molecules to form a network structure, thereby enhancing the compressive strength of the permeable concrete.

[0022] The method for preparing the above-mentioned luminous permeable concrete comprises the following steps: S1: Mix cement, water reducing agent, hydrophobic agent, epoxy resin, silane coupling agent and modified luminescent powder, add water and stir at a speed of 20-30r / min, and stir evenly to obtain a premix; S2: After mixing small-size coarse aggregate, large-size coarse aggregate and fly ash, add the premix and stir evenly at 20-30r / min to obtain luminous permeable concrete; S3: Pour in layers with a thickness of 100mm per layer, use a flat vibrator or a light vibrating rod for vibration compaction, and spray and cover for curing after pouring.

[0023] Beneficial effects of the present invention: 1. The present invention adopts coarse aggregate with interval grading to increase the contact points between aggregates, forming a stable and uniform pore structure, taking into account the compressive strength and water permeability of the luminous permeable concrete; 2. The luminescent powder added to the concrete during the mixing process adopted by the present invention has a silicon dioxide coating layer and a sodium borate heat stabilizer. The silicon dioxide coating layer provides a hydrophobic isolation layer and an anti-corrosion layer for the luminescent powder, avoids hydrolysis reaction and ensures the chemical stability of the luminescent powder in a strong alkaline environment; sodium borate is used as a heat stabilizer to reduce the non-radiative transition caused by thermal motion in the high-temperature environment of the hydration of the luminescent powder concrete, and the luminescent permeable concrete doped with the luminescent powder has stable luminescent performance, good overall durability and long service life; 3. The present invention adopts aminosulfonate-based high-efficiency water-reducing agent to improve the compressive strength of luminous permeable concrete; utilizes silanol generated by hydrolysis of tridecafluorooctyltrimethoxysilane to form a hydrophobic film to improve the anti-seepage and hydrophobic performance of the internal pores of the luminous permeable concrete; the low surface energy fluorocarbon chain contained in the tridecafluorooctyltrimethoxysilane molecule provides oleophobic performance for the luminous permeable concrete; silanol reacts with the hydroxyl groups on the surface of the concrete to form a silicon-oxygen bond, which is conducive to the entanglement between molecules to form a network structure, thereby improving the stability and high temperature resistance of the permeable concrete. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0025] The sources and / or properties of the raw materials used in the embodiments of the present invention and the comparative examples are as follows: the cement adopts Washi P.O42.5 silicate cement produced by Wuhan Yangluo Cement Plant; the small-size coarse aggregate adopts limestone crushed stone with a particle size of 5-10 mm produced by Lingshou County Xinyi Mineral Products Processing Plant; the large-size coarse aggregate adopts granite crushed stone with a particle size of 15-20 mm produced by Lingshou County Xinyi Mineral Products Processing Plant; the aminosulfonate-based high-efficiency water reducer adopts the aminosulfonate-based high-efficiency water reducer produced by Laiwu Yanhui Building Materials Co., Ltd.; the tridecafluorooctyl trimethoxysilane adopts the tridecafluorooctyl trimethoxysilane produced by Changzhou Kefeng Chemical Co., Ltd.; the epoxy resin Bisphenol A epoxy resin from Hyde New Materials Co., Ltd. was used; γ-aminopropyl triethoxysilane model KH-550 from Dewar Chemical (Shanghai) Co., Ltd. was used as silane coupling agent; ethyl orthosilicate was ethyl orthosilicate from Shanghai Zhuorui Chemical Co., Ltd.; anhydrous ethanol was anhydrous ethanol from Yonghua Chemical Technology (Jiangsu) Co., Ltd.; luminescent powder was strontium silicate luminescent powder and strontium aluminate luminescent powder from Micron Electromechanical Engineering (Nantong) Co., Ltd.; the preparation steps of the modified luminescent powder are as follows: S1: dissolving tetraethyl orthosilicate in anhydrous ethanol, adding nitric acid as a catalyst for hydrolysis reaction, and stirring and mixing thoroughly to form silica sol; S2: Strontium silicate luminescent powder and strontium aluminate luminescent powder are mixed in a ratio of 1:1 and added to the silica sol in batches, and ammonia water is added to adjust the pH to 9-10, and the mixture is stirred at 75-90°C for 0.5-1h for polycondensation to form silica gel. The silica gel aggregates on the surface of the luminescent powder and forms a dense coating layer, which is filtered and dried to obtain the coated luminescent powder; S3: Slowly add 10-20% sodium borate solution of half the mass of the coated luminescent powder into the above-mentioned coated luminescent powder, stirring while adding, mix evenly at a temperature of 100-150°C, and dry to obtain a modified luminescent powder.

[0026] Example 1: A luminous permeable concrete, the specific preparation steps are as follows: S1: 280g of Portland cement, 4g of aminosulfonate-based high-efficiency water reducing agent, 20g of tridecafluorooctyl trimethoxysilane, 30g of bisphenol A epoxy resin, 3g of γ-aminopropyl triethoxysilane and 70g of modified luminescent powder were mixed, and water was added while stirring at a speed of 20-30r / min to obtain a premix after stirring evenly; S2: Mix 290g of limestone crushed stone with a particle size of 5-10mm, 580g of granite crushed stone with a particle size of 15-20mm and 30g of fly ash, add the premix and stir evenly at 20-30r / min for 4-6min to obtain luminous permeable concrete.

[0027] Example 2: A luminous permeable concrete, the specific preparation steps are as follows: S1: 290g of silicate cement, 5g of aminosulfonate-based high-efficiency water reducing agent, 25g of tridecafluorooctyl trimethoxysilane, 35g of bisphenol A epoxy resin, 4g of γ-aminopropyl triethoxysilane and 75g of modified luminescent powder were mixed, and water was added while stirring at a speed of 20-30r / min to obtain a premix after stirring evenly; S2: Mix 295g limestone crushed stone with a particle size of 5-10mm, 590g granite crushed stone with a particle size of 15-20mm and 35g fly ash, add the premix and stir evenly at 20-30r / min for 4-6min to obtain luminous permeable concrete. Example 3: A luminous permeable concrete, the specific preparation steps are as follows: S1: 300g of Portland cement, 6g of aminosulfonate-based high-efficiency water reducing agent, 30g of tridecafluorooctyl trimethoxysilane, 30g of bisphenol A epoxy resin, 5g of γ-aminopropyl triethoxysilane and 80g of modified luminescent powder were mixed, and water was added while stirring at a speed of 20-30r / min to obtain a premix after stirring evenly; S2: Mix 300g of limestone crushed stone with a particle size of 5-10mm, 600g of granite crushed stone with a particle size of 15-20mm and 40g of fly ash, add the premix and stir evenly at 20-30r / min for 4-6min to obtain luminous permeable concrete.

[0028] Comparative Example 1: A luminous permeable concrete, which differs from Example 2 in that 295 g of limestone crushed stone with a particle size of 5 to 10 mm is replaced with 295 g of granite crushed stone with a particle size of 15 to 20 mm.

[0029] Comparative Example 2: A luminous permeable concrete, which differs from Example 2 in that 590 g of granite crushed stone with a particle size of 15-20 mm is replaced with 590 g of limestone crushed stone with a particle size of 5-10 mm.

[0030] Comparative Example 3: A luminous permeable concrete, which differs from Example 2 in that 75 g of modified luminous powder is replaced by 75 g of unprocessed ordinary luminous powder.

[0031] Performance Test: 1. Compressive strength: The concrete obtained in the embodiment and the comparative example was poured into a mold of 150 mm × 150 mm × 600 mm, and the square brick samples were obtained after curing for 28 days. The compressive properties of the square brick samples obtained in the embodiment and the comparative example were tested according to the compressive strength test in GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the test results are shown in Table 1.

[0032] 2. Water permeability coefficient: According to the water permeability coefficient test method in Appendix A of "JC / T 2558-2020 Permeable Concrete", the water permeability coefficient of the luminous permeable concrete test blocks prepared in the embodiment and the comparative example was tested, and the test results are shown in Table 1.

[0033] 3. Luminescence performance test: The luminous permeable concrete cured for 28 days was irradiated with sunlight for 1 hour and then placed in a dark room to test its luminescence time. The results are shown in Table 1.

[0034]

[0035] Data Analysis: It can be seen from Examples 1 to 3 that the luminous permeable concrete of the present invention has both compressive strength and water permeability. Its compressive strength is not less than 26.8 MPa, and its water permeability coefficient is not less than 17.4 mm / s. At the same time, its luminous performance is also excellent. The minimum luminous time is 6.8 hours after 1 hour of sunlight irradiation, which meets the night luminous requirements.

[0036] It can be seen from Example 2 and Comparative Examples 1-2 that the compressive strength of Example 2 is increased by 47% compared with that of Comparative Example 1, while the water permeability coefficient is only reduced by 16.8%, which indicates that the interval-graded luminous concrete can obtain a greater improvement in compressive strength by sacrificing a small part of the water permeability compared with the single large-particle coarse aggregate luminous permeable concrete; the water permeability coefficient of Example 2 is increased by 67.9% compared with Comparative Example 2, and the compressive strength is only reduced by 21.6%, which indicates that the interval-graded luminous concrete can obtain a greater improvement in water permeability by sacrificing a small part of the compressive strength compared with the single small-particle fine aggregate luminous permeable concrete; on the whole, compared with the single-graded coarse aggregate, the design of the interval-graded coarse aggregate can better take into account both compressive strength and water permeability.

[0037] It can be seen from Example 2 and Comparative Example 3 that the modified luminescent powder used in the present invention has better luminescent performance than the unprocessed luminescent powder. This is because the hydrophobicity provided by the silica coating layer avoids the partial hydrolysis reaction of the luminescent powder during the concrete mixing process, and the anti-corrosion layer provided maintains the chemical stability of the luminescent powder in the strong alkaline environment of concrete mixing. The sodium borate decomposes to form a borate glassy substance as a high-temperature protective layer, which effectively reduces the non-radiative transition caused by the thermal motion of the luminescent powder during the concrete hydration process.

Claims

1. A luminous permeable concrete, characterized in that: Prepared from the following raw materials in parts by weight: 280-300 parts of cement, 870-900 parts of interval graded coarse aggregate, 70-80 parts of modified luminescent powder, 30-40 parts of fly ash, 4-6 parts of water reducer, 20-30 parts of hydrophobic agent, 30-40 parts of epoxy resin, 3-5 parts of silane coupling agent and 90-100 parts of water; The interval-graded coarse aggregate is prepared by mixing coarse aggregate with a small particle size of 4.95-9 mm and coarse aggregate with a large particle size of 12.5-10 mm, and the mass ratio of the small particle size coarse aggregate to the large particle size coarse aggregate is 1:2; The modified luminescent powder is prepared by mixing strontium silicate and strontium aluminate, wherein the mass ratio of strontium silicate to strontium aluminate is 1:

1. The surface of the modified luminescent powder is coated with silica sol, and sodium borate is added for heat resistance treatment.

2. The luminous permeable concrete according to claim 1, characterized in that: The cement is silicate cement.

3. The luminous permeable concrete according to claim 1, characterized in that: The small-size coarse aggregate is at least one of limestone and sandstone, and the large-size coarse aggregate is at least one of granite, dolomite and cedar.

4. The luminous permeable concrete according to claim 1, characterized in that: The fly ash is Class II fly ash.

5. The luminous permeable concrete according to claim 1, characterized in that: The water reducer is an aminosulfonate-based high-efficiency water reducer.

6. The luminous permeable concrete according to claim 1, characterized in that: The hydrophobic agent is tridecafluorooctyltrimethoxysilane.

7. The luminous permeable concrete according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin, and the silane coupling agent is at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and methacryloxysilane.

8. The luminous permeable concrete according to claim 1, characterized in that: The steps for preparing the modified luminescent powder are as follows: S1: dissolving tetraethyl orthosilicate in anhydrous ethanol, adding hydrochloric acid as a catalyst for hydrolysis reaction, and stirring and mixing thoroughly to form silica sol; S2: Strontium silicate luminescent powder and strontium aluminate luminescent powder are mixed in a ratio of 1:1 and added to the silica sol in batches, and ammonia water is added to adjust the pH to 9-10. The mixture is stirred at 75-90°C for 0.5-1h for polycondensation to form silica gel. The silica gel aggregates on the surface of the luminescent powder and forms a dense coating layer, which is filtered and dried to obtain the coated luminescent powder. S3: Slowly add 10-20% sodium borate solution of half the mass of the coated luminescent powder into the above-mentioned coated luminescent powder, stirring while adding, mix evenly at a temperature of 100-150°C, and dry to obtain a modified luminescent powder.

9. A method for preparing luminous permeable concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Mix cement, water reducing agent, hydrophobic agent, epoxy resin, silane coupling agent and modified luminescent powder, add water and stir at a speed of 20-30r / min, and stir evenly to obtain a premix; S2: After mixing small-size coarse aggregate, large-size coarse aggregate and fly ash, add the premix and stir evenly at 20-30r / min to obtain luminous permeable concrete; S3: Pour in layers with a thickness of 100mm per layer, use a flat vibrator or a light vibrating rod for vibration compaction, and spray and cover for curing after pouring.

Citation Information

Patent Citations

  • Colorful luminous pervious concrete and preparation method thereof

    CN117383874A

  • Waterborne energy-storage luminescent paint for road as well as preparation method and application of waterborne energy-storage luminescent paint

    CN118206905A

Cited By

  • Composite asphalt regenerant based on silane modified amido amine and preparation method of composite asphalt regenerant

    CN121182139A

  • High-impermeability durable mineral-doped sludge curing agent and preparation method thereof

    CN122355651A

  • High-impervious durable mineral blended sludge solidifying agent and preparation method thereof

    CN122355651B